Changes in the Clinical Workforce Providing Contraception and Abortion Care in the US, 2019–2021. Issue 2 (February 2023) - Strasser, Julia; Schenk, Ellen; Dewhurst, Emma; Chen, Candice
ABSTRACT: A clinical workforce providing contraceptive and abortion care is critical for access to contraception and may include women's health, primary care, and other clinicians. A confluence of crises faced by clinicians may be associated with their loss from the workforce. Such crises include COVID-19 and policies penalizing abortion care, which culminated in the 2022 Dobbs v Jackson decision overturning Roe v Wade . This study used a national-level claims data set to examine changes in the contraception and abortion workforce from January 2019 to December 2021. IQVIA preadjudicated medical claims were derived from clinician offices and insurance clearinghouses. Data were obtained on contraceptive methods (intrauterine devices, contraceptive implants, injectable contraception), abortion (ie, misoprostol and mifepristone, dilation and curettage, dilation and evacuation, and surgical procedures), or both. Outcome variables examined included counts of contraceptive and abortion clinicians by year and service type and monthly volume changes in services. During the study period, 141, 837 clinicians provided at least 1 in-person contraception or abortion service, and 5804 provided both. In 2020, the number of physicians in the workforce decreased for all services except medical abortion, and the number of physicians providing contraceptive care was not reestablished to prepandemic levels in 2021. Abortion services did not distinctly decrease in early 2020. Instead, procedural abortion steadily decreased (from 8315 services in January 2019 to 5665 services in December 2021), and use of medication abortions steadily increased (from 14, 347 services in January 2019 to 16, 074 services in December 2021). In contrast, the number of advanced practice clinicians (physician assistants, nurse practitioners) was identical from 2019 to 2020 and increased above prepandemic levels in 2021. Abortion services did not distinctly decrease in early 2020. Instead, procedural abortion steadily decreased (from 8315 services in January 2019 to 5665 services in December 2021), and medication abortions steadily increased (from 14, 347 services in January 2019 to 16, 074 services in December 2021). The incredible strain on the health workforce by COVID-19 resulted in practice closures and physicians leaving practice. Although these physicians may reenter the workforce, the data suggest ongoing loss of physicians providing contraception services. Access to contraception requires that primary care clinicians offer the full scope of care, including family planning services. State-level expanded scope of practice policies may strengthen this segment of the workforce. These data show that the overall number of clinicians providing contraception and abortion services decreased in 2020 and was restored in 2021. The number of physicians providing contraception services did not reach prepandemic levels, whereas the number of advanced practice clinicians providing contraception services continued to increase, which mirrored the increasing numbers of advanced practice clinicians in primary care and other settings. Many individuals reported fertility plans for fewer children or later pregnancies, suggesting that demand for contraceptive services remained even as services were unavailable. In addition, this study did not capture outcomes associated with the 2022 Supreme Court decision overturning Roe v Wade, a watershed event that will shape the provision of abortion and contraception for the foreseeable future.